Planning and Implementing a Successful NSA-NSF GenCyber Summer Cyber Academy - Bryson R. Payne; Tamirat Abegaz; Keith Antonia (Journal of Cybersecurity Education, Research & Practice)
The GenCyber program is jointly sponsored by the National Security Agency (NSA) and the National Science Foundation (NSF) to help faculty and cybersecurity experts provide summer cybersecurity camp experiences for K-12 students and teachers. The main objective of the program is to attract, educate, and motivate a new generation of young men and women to help address the nationwide shortage of trained cybersecurity professionals. The curriculum is flexible and centers on ten cybersecurity first principles. Currently, GenCyber provides cyber camp options for three types of audiences: students, teachers, and a combination of both teachers and students. In 2016, over 120 GenCyber camps were funded, serving 5,000+ students and teachers, and the NSA hopes to double the program in 2017. GenCyber camps can be offered at colleges, universities, public or private school systems, or non-profit institutions. The purpose of this paper is to describe the GenCyber program, provide lessons learned from a successful program implementation, and encourage PI’s to plan and implement a GenCyber summer cyber academy.